CDK7/12/13 inhibition targets an oscillating leukemia stem cell network and synergizes with venetoclax in acute myeloid leukemia - He, Lixiazi; Arnold, Christian; Thoma, Judith; Rohde, Christian; Kholmatov, Maksim; Garg, Swati; Hsiao, Cheng‐Chih; Viol, Linda; Zhang, Kaiqing; Sun, Rui; Schmidt, Christina; Janssen, Maike; et al. (EMBO molecular medicine, 2022)
The heterogeneous response of acute myeloid leukemia (AML) to current anti-leukemic therapies is only partially explained by mutational heterogeneity. We previously identified GPR56 as a surface marker associated with poor outcome across genetic groups, which characterizes two leukemia stem cell (LSC)-enriched compartments with different self-renewal capacities. How these compartments self-renew remained unclear. Here, we show that GPR56+ LSC compartments are promoted in a complex network involving epithelial-to-mesenchymal transition (EMT) regulators besides Rho, Wnt, and Hedgehog (Hh) signaling. Unexpectedly, Wnt pathway inhibition increased the more immature, slowly cycling GPR56+CD34+ fraction and Hh/EMT gene expression, while Wnt activation caused opposite effects. Our data suggest that the crucial role of GPR56 lies in its ability to co-activate these opposing signals, thus ensuring the constant supply of both LSC subsets. We show that CDK7 inhibitors suppress both LSC-enriched subsets in vivo and synergize with the Bcl-2 inhibitor venetoclax. Our data establish reciprocal transition between LSC compartments as a novel concept underlying the poor outcome in GPR56high AML and propose combined CDK7 and Bcl-2 inhibition as LSC-directed therapy in this disease.
Gesehen am 25.11.2024